Welcome to Westonci.ca, where curiosity meets expertise. Ask any question and receive fast, accurate answers from our knowledgeable community. Join our platform to connect with experts ready to provide accurate answers to your questions in various fields. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.

What is the derivative of g(x)=e^(x^2+2x)+3x

Sagot :

Ok first we can split it in two : [tex]e^{x^2+2x}[/tex] and [tex]3x[/tex].

The derivative of [tex]3x[/tex] is 3.

For the first part, we use the chain rule : [tex][f(g(x))]'=g'(x)f'(g(x))[/tex] hence [tex](e^{x^2+2x})'=(x^2+2x)'e^{x^2+2x}[/tex] (since the derivative of the exponential is itself) hence [tex]g'(x)=(2x+2)e^{x^2+2x}+3[/tex]
[tex]g(x)=e^{x^2+2x}+3x\\ g'(x)=e^{x^2+2x}\cdot(2x+2)+3\\ g'(x)=2e^{x^2+2x}(x+1)+3 [/tex]